Green Accounting and Financial Performance: A Study of Environmentally-Oriented Companies - Muhammad Hasyim Ashari (PT. Hafasy Dwi Nawasena, 2026)
This study examines the relationship between green accounting practices and the financial performance of environmentally-oriented companies. As sustainability becomes increasingly central to corporate strategy, understanding how environmental cost disclosure, environmental performance, and corporate social responsibility (CSR) reporting interact with profitability metrics is of growing importance. Drawing on a review of recent empirical literature spanning 2021–2026 and focusing on companies listed on major stock exchanges that have adopted environmental management frameworks, this article develops a conceptual model linking three key independent variables — green accounting disclosure, environmental performance (proxied by PROPER ratings), and CSR disclosure — to financial performance outcomes measured by Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM). The findings suggest that green accounting and environmental performance exert significant positive effects on financial performance, while CSR disclosure shows mixed results depending on industry context. These results affirm the business case for environmental accountability and contribute to the growing body of literature on sustainable finance and green management accounting.